2021
DOI: 10.1007/s00030-021-00677-9
|View full text |Cite
|
Sign up to set email alerts
|

Approaching optimality in blow-up results for Keller–Segel systems with logistic-type dampening

Abstract: Nonnegative solutions of the Neumann initial-boundary value problem for the chemotaxis system in smooth bounded domains $$\Omega \subset {\mathbb {R}}^n$$ Ω ⊂ R n , $$n \ge 1$$ n ≥ 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…• In the system (1.1), when D(u) = 1, S(u) = u and f (u) = u, Winkler [22] showed that if 1 < κ < 3 2 + 1 2n−2 (n ≥ 5), then there exists a solution blowing up in finite time; Moreover, a similar blow-up result was obtained in the case that D(u) = (u + 1) m−1 with m ≥ 1 in [2]; Furthermore, Fuest [5] showed that solutions blow up in finite time under the conditions that 1 < κ < min 2, n 2 and µ > 0 (n ≥ 3) and that κ = 2 and µ ∈ 0, n−4 n (n ≥ 5); In the two dimensional setting and κ = 2, global existence and boundedness were established when Ω u 0 < 8π, whereas finite-time blow-up occurs when Ω u 0 < m 0 with m 0 > 8π in [4].…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…• In the system (1.1), when D(u) = 1, S(u) = u and f (u) = u, Winkler [22] showed that if 1 < κ < 3 2 + 1 2n−2 (n ≥ 5), then there exists a solution blowing up in finite time; Moreover, a similar blow-up result was obtained in the case that D(u) = (u + 1) m−1 with m ≥ 1 in [2]; Furthermore, Fuest [5] showed that solutions blow up in finite time under the conditions that 1 < κ < min 2, n 2 and µ > 0 (n ≥ 3) and that κ = 2 and µ ∈ 0, n−4 n (n ≥ 5); In the two dimensional setting and κ = 2, global existence and boundedness were established when Ω u 0 < 8π, whereas finite-time blow-up occurs when Ω u 0 < m 0 with m 0 > 8π in [4].…”
Section: Introductionmentioning
confidence: 73%
“…In [5,19,23] the critical values such that solutions remain bounded or blow up in finite time were derived. With regard to the conditions (1.9), (1.13) and (1.…”
Section: Open Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in the resulting version of (1.1) with u ≡ 0 any choice of μ > 0 is sufficient to suppress any blow-up phenomenon in two-dimensional initial value problems in the sense that for widely arbitrary initial data, global bounded solutions always exist ( [41,45]); in associated three-and higher-dimensional counterparts, however, similar findings on exclusion of explosions to date seem to rely on the stronger hypothesis that μ > μ 0 with some μ 0 = μ 0 ( ) > 0 ( [53,61]), while for small values of μ > 0 only some weak solutions are known to exist globally ( [32]). Although some studies concerned with simplified model variants have revealed some considerably strong singularity-counteracting effects of logistic damping in the sense of immediate regularization of strongly singular distributions ( [33,60]), not only results on possibly transient emergence of high population densities ( [24,56]), but moreover especially some detections of genuine blow-up both in high-dimensional systems with quadratic zero-order dissipation ( [12]), and in three-dimensional models involving some subquadratic but yet superlinear absorption ( [12]), indicate some persistence of taxis-driven destabilization also in the presence of such degradation mechanisms.…”
Section: Introductionmentioning
confidence: 99%